Vitamin D2 at high and low concentrations exert opposing effects on molecular order and dynamics of dipalmitoyl phosphatidylcholine membranes. Issue 2 (2001) - Kazanci Kazanci, Nadide Nadide; Toyran Toyran, Neslihan Neslihan; Haris Haris, Parvez I. Parvez I.; Severcan Severcan, Feride Feride
Abstract : Fourier Transform Infrared spectroscopic studies show that low concentrations of vitamin D2 (1 and 3 mol %) does not induce significant change in the overall shape of the thermotropic profile of dipalmitoyl phosphatidylcholine (DPPC) membrane. In contrast, at higher concentrations of vitamin D2 (9 and 12 mol %), the phase transition shifts to lower temperatures and a significant broadening in the phase transition curve is also observed. Low concentration of vitamin D2 decreases the frequency of the CH2 stretching mode, implying an ordering effect, whilst high concentration of vitamin D2 disorders the system. Furthermore, at low and high concentrations, vitamin D2 causes opposing effect on membrane dynamics. It decreases the bandwidth of the CH2 stretching modes at low concentrations while increasing it at high concentrations. We have also observed different actions of vitamin D2 at low and high concentrations in the deep interior and interfacial region of the membrane, by monitoring the frequency of the CH3 stretching band and C=O stretching bands, respectively.